ปัจจัยที่มีอิทธิพลต่อการมีส่วนร่วมของประชาชนในการจัดการ ขยะมูลฝอยในเขตพื้นที่เทศบาลตำบลบ้านสา อำเภอแจ้ห่ม จังหวัดลำปาง - มะลิวัลย์ ฝันมะติ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The study “Factors Influencing Solid Waste Management Participation in Tambon Bansa Municipality, Chae Hom District, Lampang Province” aimed to investigate factors affecting the waste management participation of the citizen in Tambon Bansa Municipality, Chae Hom Distric, Lampang Province and to examine the problems, obstacles and suggestions in the participation of the citizen in managing the waste in Tambon Bansa.This quantitative research employed the survey research methodology which included 200 citizen of Tambon Bansa completed the questionnaires and 12 community leaders participated in the interviews. From the data, it was found that the roles of the administrators and community leaders in participating in the waste management were publicizing the waste policies through meetings, public relations, persuasions, and being role models in participation in the project. Also they followed up the results, solved the problems and obstacles, and pushed forward the project to operate smoothly. Moreover, the data indicated that the community leaders used wire broadcasting to push forward the waste management project in the villages. Therefore, the villagers learned about the progress of the sales of the waste, time period and other details. Consequently, the citizen realized the significance and benefits of waste sorting. They also became aware of its benefits to the community in making the village clean and pleasant. Furthermore, in motivating the citizen to manage the waste, there was the building of knowledge, understanding and awareness of the benefits of sorting the waste before selling. In addition, there was the application to participate in the local waste management project with the Municipality. The most influential factors affecting the waste management participation of the citizen was the project included the competition and reward components; for example, prize money, certificates, and appraisal for the families and villages participated with the highest waste sales and sorted the waste regularly. Finally, the waste management of the Municipality included the campaign promoting the citizen to put the sorted waste in the bags provided by the Municipality for the collection on the designated dates and locations in the village. Also the Municipality charged 20 Baht each month. The data revealed that the satisfaction level of the citizen was at an average level. The citizen thought that waste collection was the responsibility of the Municipality to make it effective with reasonable fee and improve its management. In terms of problems and obstacles, it was found that since the Municipality had the participatory waste management center at Tambon Bansa Municipality by selling the Refuse Derived Fuel (RDF) produced from the sorted waste to The Siam Cement Public Company Limited (Lampang), some families did not seriously sort the waste before putting it in the provided bags. They mixed the stones, brick, concrete debris, tiles, twigs, leaves, and hazardous waste. Moreover, the policy of the Municipality’s administrator was to put the waste in front of their houses and in the villages. However, some families did not put the waste in the bags before they disposed the waste causing odor, insect, and cleanness problems. Consequently, there was a delay in the waste management in the community.